A Study on Dengue Infection among Febrile Illness Cases in a Tertiary Care Hospital in South India - Dr. M. Bharathi, Dr. Naga Srilatha Bathala, Dr. S. Kusuma bai; Sasidhar, Dr. M.; Sasikala, Dr. A. (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Dengue is the most important arthropod-borne viral disease of public health significance. Dengue virus has been prevalent in the Indian subcontinent for the last 50 years and has become hyper-endemic with circulation of all the four serotypes. The disease follows seasonal and cyclical patterns with large outbreaks occurring every two to three years. Dengue affected children are known to have serious disease outcome. As there is no prevention in the form of any vaccine for dengue, early diagnosis and treatment is recommended for preventing complications. Aims and objectives: 1. To know IgM positivity of dengue virus among febrile illness cases. 2. To know the most common age group affected with dengue virus. Material and Methods: The study was undertaken for a period of one year from January 2015 to December 2015. Blood samples from 4045 patients admitted with febrile illness were tested for IgM of dengue virus by MACELISA. Results: Total numbers of cases tested for IgM antibody were 4045. More number of samples (39.5%) were in November. Majority of the samples were from the age group of 11-20yrs (25.8%) and <10 yrs (24.6%). More positive samples were in the month of October (68/235). But the percentage of positivity was high in the months of March (24.1%) and April (20%). The overall positivity for IgM antibody of dengue virus was 5.8%. Throughout the year dengue positive cases were seen among in patients. High positivity was seen in the < 10 years age group both in males and females. Conclusions: 1. Most common affected age group with dengue infection was < 10 years. 2. Male were more affected with dengue infection than females. 3. Dengue virus is endemic in our area.